Pengaruh Human Resource Development dan Organizational Culture Terhadap Kinerja Pegawai pada Kantor Pemadam Kebakaran di Tabanan - Prameliani, Ni Luh Rizka; Sri Hartati, Ni Putu; Mashyuni, I.A (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to find out the influence of human resource development and organizational culture partially and simultaneously on employee performance. The location of this research at the Fire Department in Tabanan, the sample used as many as 106 respondents. Data collection is carried out through observations, interviews, documentation, literature, and questionnaires. The data analysis techniques used are Validity Test, Rehabilitation, Classical Assumptions, Multiple Linear Regression, Determination Coefficient, t Test and F Test. Based on the results of the study, it can be seen that: (1) human resource development has a significant positive effect on employee performance, where a value of t 4,618 and sig 0.000 is obtained. (2) organizational culture has a significant positive effect on employee performance, where a value of t 3,880 and sig 0.000 is obtained. (3) simultaneously human resource development and organizational culture have a significant effect on employee performance, where a value of F 56,260 is obtained and a significance of 0.000. The magnitude of the influence of free variables on employee performance is 51.3%. The advice that can be given by researchers is that the Fire Department in Tabanan is expected to routinely provide training to employees and leaders of the Fire Department in Tabanan should always try to provide solutions to problems faced by employees.